Akibat hukum terhadap jual beli tanah yang telah didahului perjanjian nominee dengan warga negara asing - Norentia Ekunming Sari; Suhariningsih Suhariningsih; Abdul Madjid (University of Merdeka Malang, 2021)
This article has the intent and purpose of the nominee agreement regarding land rights in Indonesia. This happens because many foreign nationals, hereinafter referred to as foreigners, can own land in Indonesia, while positive law in Indonesia only allows Indonesian citizens who can own land ownership rights in Indonesia. The nominee agreement is legal smuggling that can result in land being returned to the state. However, in the Decision of the Denpasar District Court in 2013 Number 82/PDT.G/2013/PN.DPS, one of the judges' decisions is that land must be resold and the proceeds from the sale of land are divided between foreigners (benefactors) and Indonesian citizens (legal owners) as comparison in a case approach to analyze the sale and purchase of land that has been preceded by a nominee agreement in Indonesia. the action of the Plaintiff who is a foreigner to sell the land and buildings prior to the lawsuit is one of the considerations for the judge in deciding this case. In addition, Defendant I sold the land below the market price. Therefore, the unlawful acts committed by Defendant I and Defendant II over the sale and purchase of rights to the object of the dispute must be accounted for by the Defendants.How to cite item: Sari, N., Suhariningsih, S., Madjid, A. (2021). Akibat hukum terhadap jual beli tanah yang telah didahului perjanjian nominee dengan warga negara asing. Jurnal Cakrawala Hukum, 12(2), 205-212. doi:https://doi.org/10.26905/idjch.v12i2.5808